ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN AL-QUR'AN HADITS: STUDI KASUS MTsN 6 DAN MAN 2 KOTA PADANG - Hasanah, Uswatun; Nelawati, Sasmi; Khadijah, Khadijah (PAI RAFAH, 2023)
The context underlying this research relates to the current state of education, which has not yet established its own identity. The curriculum has undergone continuous modifications, leading to the development of an independent curriculum. Several problems began to emerge, especially among educators who had a significant impact on the learning process. This research aims to analyze the establishment of an independent curriculum at the school level. This research uses a qualitative approach with phenomenological methods. The qualitative design was applied to two schools in Padang City. The data collection techniques used were interviews and document analysis. Data analysis was conducted using an interactive model that included data reduction, data presentation, and data conclusion. Based on the research conducted, it appears that the application of the independent curriculum at MTsN 6 and MAN 2 Padang City in learning Al-Qur'an Hadith has only been implemented for the last six months. The independent curriculum of MTsN 6 is applied to class VII and at MAN 2 it is applied to class X. The problems in implementing the independent curriculum in these two schools include the teaching material of curriculum 13 to the independent curriculum leveling up, limited training in processing teaching modules, time management challenges, gaps in access to learning, and lack of interest of students in memorizing the Qur'an and Hadith. It can be said that the implementation of the independent curriculum in the Al-Qur'an Hadith subject has not been well implemented.